2022
DOI: 10.1093/aob/mcac063
|View full text |Cite
|
Sign up to set email alerts
|

Kinetochore size scales with chromosome size in bimodal karyotypes of Agavoideae

Abstract: Background and Aims In eukaryotes, the total kinetochore size (defined as a chromosomal region containing CENH3-positive nucleosomes) per nucleus strongly correlates with genome size, a relationship that has been hypothesized to stem from general intracellular scaling principles. However, it could also come from the mechanics of the cell division, if larger chromosomes within a karyotype required larger kinetochores to move properly. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Species with large genomes and few chromosomes have the largest centromeres (e.g., rye), while species with small genomes and many chromosomes have the smallest centromeres (e.g., rice) (Zhang and Dawe 2012). Although not as obvious as between species, a positive correlation between kinetochore size and chromosome size was also observed in human (Irvine et al 2004) and maize (Wang et al 2021), and within bimodal karyotypes as demonstrated for Agavoideae species (Plačková et al 2022).…”
Section: Topo Iiα and Cenh3 Are Part Of The (Peri)centromeric Chromatinmentioning
confidence: 81%
See 1 more Smart Citation
“…Species with large genomes and few chromosomes have the largest centromeres (e.g., rye), while species with small genomes and many chromosomes have the smallest centromeres (e.g., rice) (Zhang and Dawe 2012). Although not as obvious as between species, a positive correlation between kinetochore size and chromosome size was also observed in human (Irvine et al 2004) and maize (Wang et al 2021), and within bimodal karyotypes as demonstrated for Agavoideae species (Plačková et al 2022).…”
Section: Topo Iiα and Cenh3 Are Part Of The (Peri)centromeric Chromatinmentioning
confidence: 81%
“…A positive correlation exists between kinetochore and chromosome size, and the adequate number of attached microtubule spindle fibers are important for correct chromosome segregation during cell division. Larger chromosomes require more microtubules, and thus larger kinetochores to move them with the same velocity as small ones (Nicklas 1965;Plačková et al 2022). The microtubule-binding capacity increases with kinetochore size in Indian muntjac chromosomes (Drpic et al 2018) and in rat-kangaroo PtK1 cells, and it was demonstrated that the chromosome size determines the number of microtubules (McEwen et al 1998).…”
Section: Topo Iiα and Cenh3 Are Part Of The (Peri)centromeric Chromatinmentioning
confidence: 99%
“…Although there are general trends in the distribution of (relative) chromosome sizes, the true physical length of a chromosome may not be the main factor that determines the rearrangement dynamics but rather its genomic content. Firstly, kinetochore length (and thereby strength of attachment of the centromere to the mitotic spindle) does not scale linearly with chromosome size (Plačková et al, 2022). Indeed, variation in centromere strength may influence which karyotype changes fix in a population through meiotic drive (Chmátal et al, 2014).…”
Section: One Genome Size Does Not Fit Allmentioning
confidence: 99%